PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DIVISI ANTARAN DI PT. POS INDONESIA CABANG BATAM - Dendi Prawira; Ramon Zamora; Tibrani Tibrani (University of Riau Kepulauan, 2015)
In this study, the authors intend to answer some unifying thought that the research that you want to answer through this study is: Does motivation affect the Employee Performance, Is Work Discipline influence on employee performance. Do Motivation and Discipline Working together affect the Employee Performance Division conduction in PT.Pos Indonesia Batam Branch. Results of this study, namely Motivation does not have a positive and significant influence on Employee Performance Division conduction in PT.Pos Indonesia Batam Branch of 1,121 1.671 and 0.267 0.05 insignificant. Work and Discipline has a positive and significant impact on Employee Performance Division conduction in PT.Pos Indonesia Batam Branch of 7.102 1.671 and 0.000 0.05 was very significant. As well as Motivation and Discipline Work together affect the Employee Performance Division conduction in PT.Pos Indonesia Batam Branch obtained value of R Square (R2) of 0.737 or 73.70%. This means the ability and discipline of work motivation variable in explaining the performance of employees is 73.70% which means very strong. The remaining portion of 26.30% is explained by other variables not included in this study.